(untitled) (Bangladesh Journal of Medical Science, 2026)
Aim is to improve the physical development and physical fitness of primary school children who are overweight through physical education. Materials and methods The study was conducted from January to May 2024 at the comprehensive school in Moscow (Russia). The pedagogical experiment involved schoolchildren who study in grades 1-4 who were diagnosed with obesity of varying degrees (72 children). Children in the experimental group did physical education with a separate instructor according to the experimental program, and schoolchildren from the control group studied in one with the rest of their class. Before and after the pedagogical experiment, all schoolchildren completed control tests that assessed their level of physical development and physical fitness. Results During the study period, the schoolchildren from the control group showed an increase in the indicators of less than 2% in the EVC, Height, Weight, BMI, Jump and Run tests (p> 0.05). In the RI test, the indicators improved from 10.3±1.6 to 9.4±0.65 (t=0.52; p>0.05), the increase was 9.6%. In the Torso test, the indicators improved by 11.5% (p> 0.05), and in the Jump Rope test, the result was higher by 14.6% (p> 0.05). In the experimental group, a reliable increase in the results was recorded in 7 of 9 tests. The smallest increase in results was noted in the Height test - 1.1% (p>0.05) and Run - 0.6% p>0.05. The EVC increased by 14.2% (p<0.05), the Weight decreased by 7.8% (p<0.05), the BMI decreased by 9% (p<0.05), in the Jump test the result improved by 9% (p<0.05). In the RI test the result improved from 10.9±1 to 7.1±0.75 (t=3; p<0.05), the increase was 53.5%, in the Torso and Jump Rope tests the indicators improved by 31.4% (p<0.05) and 38.3% (p<0.05), respectively. Conclusion The results of the study in the control group indicate the low efficiency of the standard physical education program in a comprehensive school for children aged 7-11 who have excessive weight; the program is more suitable for children who do not have health limitations. The results of the tests in the experimental group indicate the efficiency of using the experimental program for children aged 7-11 who have excessive weight. These schoolchildren should do physical education according to a special program and perform physical exercises that are feasible for them. BJMS, Vol. 25 No. 01 January’26 Page : 253-262